Sustainable Food Security Strategy: Distribution, Marketing, and Pricing of Rice Food - Adam, Rosida; Sipatu, Lindanur; Satrawan Faris, Erwan (CV. Satria Jaya, 2025)
This research aims to formulate a sustainable food security strategy that focuses on the distribution, marketing, and pricing of rice in Tojo Una-Una Regency. The research sample consisted of 82 respondents, including extreme poor households (deciles 1 and 2), rice traders, and local government agencies. The analysis method used is SWOT (Strengths, Weaknesses, Opportunities, Threats) to identify strategic positions and QSPM (Quantitative Strategic Planning Matrix) to prioritize strategic alternatives. The results of the analysis show that the food security strategy is positioned in Quadrant II (Strength-Threat), which indicates that the diversification strategy is most suitable. Based on the QSPM analysis, priority strategies are: (a) increasing access to safe and nutritious food through market interventions, (b) strengthening BULOG's role in ensuring sustainable rice availability, (c) maintaining supply and price stability, (d) controlling the Highest Retail Price (HET), and (e) ensuring effective government food distribution and reserves.